A STUDY ON FINANCIAL PERFORMANCE OF SMALL INDUSTRIES DEVELOPMENT CORPORATION OF LTD (CAHIERS MAGELLANES-NS, 2024)
Industrial development adopts new technologies, modernizes infrastructure, and creates supportive regulatory frameworks to increase a country's production, efficiency, and sustainability. It turns traditional economies into competitive industrial ones and fosters economic growth, job creation, poverty alleviation, and societal well-being. Small businesses in India make a substantial economic contribution, but they also face obstacles like poor infrastructure, regulatory barriers, and restricted funding. To solve these concerns, comprehensive policies and initiatives are required. Contributions from the Small Industries Development Corporation Ltd (SIDC Ltd) have been crucial in helping small enterprises grow, creating jobs, fighting poverty, and advancing socioeconomic development. Additionally, SIDC Ltd fosters innovation and an entrepreneurial culture through funding regulatory reforms, technology transfer, and research. Reviews of the literature emphasize the financial performance of SIDC Ltd. and stress the significance of risk mitigation, liquidity, solvency, and efficient financial management for long-term growth. These studies shed light on the operational effectiveness and financial stability of SIDC Ltd. and emphasize the necessity of strategic planning for long-term viability.